2016
DOI: 10.1016/j.jadohealth.2016.03.019
|View full text |Cite
|
Sign up to set email alerts
|

The E-cigarette Social Environment, E-cigarette Use, and Susceptibility to Cigarette Smoking

Abstract: Purpose One concern regarding the recent increase in adolescent e-cigarette use is the possibility that e-cigarettes may be used by those who might not otherwise have used cigarettes, and that dual use, or transition to cigarette use alone, may follow. Methods Questionnaire data were obtained in 2014 from 11th/12th grade students attending schools in 12 communities included in the Southern California Children’s Health Study (CHS). We evaluated the cross-sectional association between e-cigarette use, the psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 25 publications
7
86
1
Order By: Relevance
“…[7][8][9][10][11][12][13] E-cigarette users, representing several age groups and geographic locations, had 2 to 4 times the odds of indicating an intention to use cigarettes as never users, 7,8 results consistent with those we reported in the CHS. 9 To date there have been 3 reports from prospective cohort studies examining the relationship between e-cigarette use and subsequent initiation of combustible cigarette use in adolescence, including a study of 9th-grade students (mean age 14.1), 14 a second study of 9th and 10th-grade students (mean age 14.7), 15 and another small study of 16-to 26-year-olds, with few never-smoking e-cigarette users at baseline that was not able to examine associations within specific developmental periods in this age range. 16 All studies found that e-cigarette use was associated with elevated risk of initiation of combustible cigarettes.…”
supporting
confidence: 83%
“…[7][8][9][10][11][12][13] E-cigarette users, representing several age groups and geographic locations, had 2 to 4 times the odds of indicating an intention to use cigarettes as never users, 7,8 results consistent with those we reported in the CHS. 9 To date there have been 3 reports from prospective cohort studies examining the relationship between e-cigarette use and subsequent initiation of combustible cigarette use in adolescence, including a study of 9th-grade students (mean age 14.1), 14 a second study of 9th and 10th-grade students (mean age 14.7), 15 and another small study of 16-to 26-year-olds, with few never-smoking e-cigarette users at baseline that was not able to examine associations within specific developmental periods in this age range. 16 All studies found that e-cigarette use was associated with elevated risk of initiation of combustible cigarettes.…”
supporting
confidence: 83%
“…Other studies have also reported that current (last 30 day) and lifetime e-cigarette use now surpasses current and lifetime cigarette use (Johnston et al, 2016; Kenne et al, 2016; Ramo et al, 2015; Sutfin et al, 2015). Current college cigarette smokers are more likely to be current e-cigarette users than non-smokers and individuals who start using e-cigarettes, have a higher susceptibility and greater likelihood of becoming a cigarette smoker (Barrington-Trimis et al, 2016; Primack, Soneji, Stoolmiller, Fine, & Sargent, 2015; Sutfin et al, 2015). Dual users are often less motivated to quit smoking (Jorenby, Smith, Fiore, & Baker, 2016) and in college populations, dual use is related to heavier use of e-cigarettes and cigarettes and higher rates of heavy drinking (Littlefield, Gottlieb, Cohen, & Trotter, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Five longitudinal studies cited in the Surgeon General report claimed that e-cigarette use at baseline predicted smoking at follow-up [19][20][21][22][23]. However, all studies suffered from the issues discussed above.…”
Section: Youth E-cigarette Use and Smoking Ratesmentioning
confidence: 99%
“…However, all studies suffered from the issues discussed above. They only assessed ever-use [19][20][21][22] or past 30-day e-cigarette use [23] and did not assess the nicotine content of ecigarettes used. There was no evidence that adolescents were regular e-cigarette users at baseline, and no evidence that they were smoking cigarettes regularly at follow-up.…”
Section: Youth E-cigarette Use and Smoking Ratesmentioning
confidence: 99%